Pengembangan Media Pembelajaran Aplikasi Mobile Learning Berbasis Android Pada Mata Kuliah Konsep Dasar Ilmu Pengetahuan Alam - Suwar Dini Khairunisa; Gufron Amirullah; Mimin Ninawati (Jurnal Inovasi Pendidikan Dasar, 2019)
This study attempts to develop teaching materials lecture in the basic concept of natural sciences 1 matter photosynthesis in plants in the form of m-learning android based for pre-service primary school teacher and know the quality of this product. The research methodology consisted of two-stage: 1) observation and 2) research and development (R & D). Observation conducted to determine the learning process in the classroom and the use of smartphone students in the classroom. Research and development (R & D) was adapted from model of ADDIE used to develop an application m-learning. This application tried out on the second semester 71 students PGSD FKIP UHAMKA. The results showed that photosynthetic teaching materials in the form of Android-based m-learning that had been developed based on material experts found a percentage score of 80.95% with good categories, then the results of validation by media experts obtained a percentage score of 77.94% with good categories. The result of the implementation of class 2D was 90,54 % with very good categories. Next in class 2E obtained the results of the quality of media learning of 94,73 % with very good categories. The results of the data indicated that the development of the teaching material photosynthesis in the form of m-learning an android fitted for use as a source learning for pre-service primary school teacher.